2022
DOI: 10.1111/jonm.13559
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal and evaluation of the instruments measuring the nursing work environment: A systematic review

Abstract: Aims: To appraise the current instruments available for measuring the nursing work environment and re-examine the definition and construct of the nursing work environment.Background: A psychometrically sound instrument is fundamental to understanding and improving the nursing work environment. The nursing work environment is a complex construct, and its definition remains inconclusive. None of the instruments available is considered as the gold standard.Evaluation: A comprehensive searching was undertaken in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Healthcare organisations are urged to continue working towards a more diverse and inclusive WE 42 44. Although the importance of a diverse and inclusive WE is evident, we are not aware of any instrument measuring the diversity and inclusivity of healthcare employees’ WE 15 16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare organisations are urged to continue working towards a more diverse and inclusive WE 42 44. Although the importance of a diverse and inclusive WE is evident, we are not aware of any instrument measuring the diversity and inclusivity of healthcare employees’ WE 15 16…”
Section: Discussionmentioning
confidence: 99%
“…A common strategy for healthcare organisations to gain insight into employees’ perceptions of their WE is to conduct a (satisfaction) survey 14. Multiple validated questionnaires are available to assess WE, each with a slightly different area of focus, target audience or length 15 16. These questionnaires are commonly composed of statements linked to Likert-type scales that ask how much a respondent agrees with the specific statement 16.…”
Section: Introductionmentioning
confidence: 99%
“…These guidelines were initially developed to conduct systematic reviews of Patient-Reported Outcome Measures (PROMs). In recent times, these have been adapted to healthy individuals or caregiver-reported outcome measures [ 21 ]. In accordance with the guideline, two reviewers independently evaluated the content validity of each instrument in three steps.…”
Section: Methodsmentioning
confidence: 99%
“…To conduct the data synthesis, we used the COSMIN guidelines. In recent years, these guidelines, initially developed to conduct systematic reviews of patient-reported outcome measures (PROMs), have been used to assess outcomes in healthy individuals or caregivers [21]. The evaluation and synthesis process is divided into two phases: one that evaluates and summarizes the evidence on the development and validation studies' quality and one that evaluates and summarizes the evidence on the measurement properties of the instruments.…”
Section: Qualitative Evaluation Of Studies Psychometric Properties An...mentioning
confidence: 99%